(untitled) (Czech Journal of International Relations, 2002)
In Syria, the beginnings of political Islamism were connected with the Muslim Brotherhood, which resisted the Baath government and initiated armed revolt in Hama in April 1964. After Hafiz al-Asad seized power, the Muslim Brotherhood split into three factions (ultra-radicals from Hama, a radical faction in Aleppo, and an exiled Damascus moderate faction). In the years 1979-1982, the Muslim Brotherhood war radicalized and oriented towards jihad, which culminated in the Hama uprising in April 1982. However, the Syrian Islamist movement was supported not even by the Islamic revolutionary regime in Iran which, on the contrary, closed strategic partnership with the Syrian regime. The Syrian branch of the Muslim Brotherhood continued getting support from abroad, where two completely independent organizations were established in 1986: one based in Saudi Arabia, and another in Iraq under the name of the National Salvation Front of Syria. In the mid-1990s, uring his liberalization campaign, President Asad made several favourable gestures towards the Muslim Brotherhood by giving amnesty to a number of jailed Brethren. In Jordan, the beginnings of the Islamist movement were connected with the Muslim Brotherhood as well. However, Jordanian Muslim Brethren never represented a threat to the monarchist regime, they were legally active and became involved in the democratization process initiated by King Husain in 1989. On the other hand, the extremist Islamic Liberation Party, which was founded in 1953, refused to join in the democratization process. In Lebanon, political Islamism emerged only after the Lebanese civil war in the Shiite religious community. The founder of the modern Shiite political movement was Musa al-Sadr, who established the Amal party in 1974. After the mysterious disappearance of Imam Sadr in 1978, pro-Syrian Amal ceased to be considered an Islamic organization, participated in the parliamentary elections and nominated its leader as speaker of parliament. However, in 1982 the pro-Iranian radical Hizbullah movement seceded from Amal party. Hizbullah initiated terrorist actions, including kidnapping hostages in the period 1982-1992, and the spectacular suicide attacks on the American Embassy and American and French Army headquarters in Beirut. It was Syria which intervened against Hizbullah activities in 1987-1988. After the end of the Gulf War, Iran recognized the importance of Syrian engagement in Lebanon. Hizbullah reevaluated its activities, abandoned classical acts of terrorism and concentrated on armed operations aimed at terminating Israeli occupation of the ’security zone’ in southern Lebanon. Hizbullah also participated in parliamentary elections. Israel and the United States continued to label Hizbullah a terrorist organization. However, since the 1990s France has viewed Hizbullah more as a Lebanese organization struggling to liberate its motherland territory from foreign occupation. In May 2000, the Israeli army withdrew its troops from Southern Lebanon. In addition to Amal and Hizbullah, Shiite splinter-groups and smaller Sunni Islamist organizations were active in Lebanon.